Research progress on the association between mastitis and gastrointestinal microbes in dairy cows and the effect of probiotics. (December 2022) - Luo, Shuangyan; Wang, Yuxia; Kang, Xinyun; Liu, Panpan; Wang, Guiqin
Abstract: Mastitis in dairy cows affects milk quality and thereby constrains the development of the dairy industry. A clear understanding of the pathogenesis of mastitis can help its treatment. Mastitis is caused by the invasion of pathogenic bacteria into the mammary gland through the mammary ducts. However, recent studies suggested that an endogenous entero-mammary pathway in dairy cattle might also be playing an important role in regulating mastitis. Also, probiotic intervention regulating host gut microbes has become an interesting tool to control mastitis. This review discusses the association of gastrointestinal microbes with mastitis and the mechanism of action of probiotics in dairy cows to provide new ideas for the management of mastitis in large-scale dairy farms. Highlights: Mastitis in dairy cows affects milk quality and thereby constrains the development of the dairy industry. A clear understanding of the pathogenesis of mastitis can help its treatment. GI microorganisms regulate the occurrence of mastitis in dairy cows. Probiotics can be involved in mastitis control in dairy cows by rebalancing the gastrointestinal microorganisms.